The Surgical Management of Intraoperative Intracranial Artery Injury in open Skull Base Surgery - A Series of Three Cases (Bangladesh Journal of Neurosurgery, 2024)
Background: intracranial surgery is very commonly performed around the world. During   these surgeries, intraoperative injury to the major intracranial vessels is a very serious   condition. It has to be addressed promptly by either direct repair or vascular bypass.   We describe three cases where there was vascular injury during surgery which were   managed by direct repair. This implies the necessity of learning microvascular   techniques for safely perform the surgery and save the patient from neurological   deficits.Bang. J Neurosurgery 2023; 12(2): 122-124